The determinants for successful crowdfunding in Malaysia - Sum, Jing Yi; Chan, Kah Xin; Lee, Annie See Ge; Tan, Sue Yee; Wong, Yee Yin (2019)
This research attempts to investigate the impact of funding target, duration, target per capita, density, virality, minimum reward, and description on the probability of crowdfunding in Malaysia. In the research, secondary data from 2012 to 2018 was collected from Mystartr official website and logistic and probit regression analysis were employed to carry out the research. Diagnostic Checking such as expectation-prediction table and goodness-of-fit tests also employed in order to observe the performance of estimated binary model. The results showed that higher funding target and target per capita negatively associated with probability of crowdfunding success. However, higher number of supporters, virality, and minimum reward positively associated with probability of crowdfunding success. Duration unexpectedly do not have any effect on probability of crowdfunding success. In examining the effect of virality components, images significantly affect probability of crowdfunding success. Furthermore, through observing the effect of project description components, the result showed that including info (images and videos) and budget plan in a project description will lead to reduce in the probability of crowdfunding success. Through combine the components of virality and project description and distinct it into different models, Model 7 (Table 4.8) from logit regression is the most accurate and best fit with our study. Although this research has its own limitations, this study is still applicable for entrepreneurs, firms, crowdfunding platforms operator and academician on the determinants for crowdfunding success in Malaysia.